Employment and Labor Law, 10th Edition - Patrick Cihon (Cengage Learning, 2019)
Introduce today's employment and labor-relations laws to business students and others who are not majoring in legal studies with an engaging text written specifically for them -- Cihon/Castagnera's EMPLOYMENT AND LABOR LAW, 10E. This comprehensive introduction uses real case excerpts to encourage critical reasoning and to clearly illustrate how labor-related disputes arise and are resolved in today's courts. Interesting chapter features, such as The Working Law and Ethical Dilemmas, demonstrate how labor legislation and ethical decision-making impact employees at all levels of organizations. This edition highlights the latest information on issues such as minimum wage, medical-marijuana and ADA, independent contractors in the "gig economy," challenges under the NLRB and EEOC, the Fair Labor Standards Act, executive branch orders regarding undocumented immigrants and LGBTQ rights, Obamacare, the Defense of Marriage Act, and other employee-benefits developments. Discover unmatched balanced coverage within a proven, reader-friendly approach.